Effect of audio and audio-visual distraction aids in reducing anxiety during pedodontic care - Mani, Geo (Bioinformation, 2020)
The use of audio-visual and audio distraction tools can lead to the improvement of the quality of treatment and benefit both the dentist and the patient. It is of interest to evaluate the anxiety levels using audio and audio-visual distraction aids during pedodontic care. We collected data on 30 children between 6 to 12 years old. Subjects were randomly assigned into three groups of ten each. The three groups were control group, audio distraction group and audio-visual distraction group. The pulse rate of all the patients were assessed, Venham’s picture test and Venham’s Clinical Rating scale was recorded for all the subjects during the first and second visits. A statistically significant (p<0.01) difference in pulse rates was observed when audio and audio-visual groups were used during treatment. This implies that distraction aids help to reduce the levels of anxiety pedodontic care.